Noninvasive respiratory supports in ICU - Frat, Jean Pierre; Grieco, Domenico L.; De Jong, Audrey; Gibbs, Kevin; Carteaux, Guillaume; Roca, Oriol; Lemiale, Virginie; Piquilloud, Lise; Rittayamai, Nuttapol; Pisani, Lara; Hernandez, Gonzalo; Thille, Arnaud W. (Springer, 2025)
Background Noninvasive respiratory supports are routinely applied in critically ill patients with acute respiratory failure to avoid intubation and invasive mechanical ventilation, thereby reducing the risk of related complications, and to facilitate successful weaning from mechanical ventilation after extubation. They are also applied during the intubation procedure for preoxygenation with the aim of enhancing oxygenation and ensuring the safety of the procedure. Main body High-flow nasal oxygen decreases airway dead space, provides a stable concentration of inspired oxygen, generates low level of flow-dependent positive airway pressure, and optimizes comfort. Positive-pressure noninvasive supports include continuous positive-airway pressure and noninvasive ventilation and enable providing higher end-expiratory pressure, thereby further improving oxygenation. Noninvasive ventilation, but not continuous positive-airway pressure, better decreases inspiratory effort, and increases tidal volume and transpulmonary driving pressure. Conclusion High-flow nasal oxygen has become the first-line therapy in acute hypoxemic respiratory failure, while noninvasive ventilation remains the reference treatment during exacerbations of chronic obstructive pulmonary disease, in patients with respiratory acidosis. In patients requiring intubation, noninvasive ventilation is the optimal technique for preoxygenation to decrease the risk of hypoxemia, while high-flow nasal oxygen is an alternative option for non-hypoxemic patients or those with contraindications to noninvasive ventilation. After extubation in patients at high risk of reintubation, prophylactic noninvasive ventilation, eventually alternating with high-flow nasal oxygen, improves weaning outcome compared to other strategies; high-flow nasal oxygen alone outperforms conventional oxygen in low-risk patients.
Keywords: Acute respiratory failure; CPAP; High-flow oxygen; Hypercapnia; Hypoxemia; NIV; Noninvasive ventilation; Post-extubation; Preoxygenation